O uso dos gêneros textuais no ensino de matemática: uma experiência com o 6º ano do ensino fundamental - Ferreira, Nedilza Souza da Silva (2025)
This dissertation investigates the contribution of the use of textual genres in teaching the thematic unit Quantities and Measurements within the mathematics curriculum to 6th-grade elementary school students. This study is justified by the difficulty many students have shown in understanding the statements of mathematics activities; in light of this fact, we sought to explore pedagogical resources that promote reading, comprehension, and interpretation of the activities proposed in the mathematics curriculum. Thus, the research question is defined as follows: In what way can the development of a didactic sequence using different textual genres contribute to the comprehension and interpretation of basic concepts in the teaching of Mathematics in the 6th grade of Elementary School? The general objective is to design, implement, and analyze a didactic sequence involving reading practices of textual genres in Mathematics teaching in the 6th grade of Elementary School. Paulo Freire and Ubiratan D’Ambrosio were used as the theoretical framework. As an Educational Product, we present a didactic sequence structured according to the Three Pedagogical Moments, with activity proposals developed from various textual genres and carried out in six sessions, totaling ten hours. The research adopted a qualitative methodology, based on an exploratory descriptiveanalytical study, and used participant observation, questionnaires, and records produced by the students as instruments. From the Content Analysis, three categories were structured, derived from Freirean theoretical support: dialogue as an educational and methodological principle; problematization as an epistemological model for knowledge construction; and textual genres and Mathematics teaching. As a result, we observed that the integrated, dialogical, and problematized adoption of textual genres in Mathematics teaching promotes the understanding of mathematical concepts from a contextualized and problem-posing pedagogical perspective. We also noted that the teaching methodology grounded in the Three Pedagogical Moments brought the teaching process closer to students’ experiences, was anchored in constant dialogue, and proved it is crucial to understand students’ experiences. for The Educational Product linked to this dissertation is free of charge, openly accessible, and available download on the PPGECM-UPF webpage (https://www.upf.br/ppgecm/dissertacoes-e-teses/dissertacoes) and on the EduCapes Portal (http://educapes.capes.gov.br/handle/capes/1174426).